Analisis Penerapan Akuntansi Pada Usaha Mikro, Kecil, dan Menengah (UMKM) Kios Aisyah - Mohamad Reza Mahmud; Roy Hasiru; Ardiansyah Ardiansyah; Radia Hafid; Rierind Koniyo (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study examines the implementation of accounting practices in Micro, Small, and Medium Enterprises (MSMEs), focusing on Kios Aisyah, and identifies factors inhibiting their application. Employing a qualitative descriptive case study approach, data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing. The findings reveal that accounting practices at Kios Aisyah remain rudimentary, relying solely on purchase receipts and simple cash records without systematic journalizing or ledger preparation. Financial information is largely estimative and dependent on the owner’s memory, with revenue recognized on a cash basis and no formal financial statements prepared. Key barriers include limited accounting knowledge, lack of training and assistance, operational prioritization, and constraints in time and human resources. This study contributes by providing an in-depth analysis of the accounting cycle implementation in micro-scale kiosk businesses.